Evidence for a dimensionality crossover at the disappearance of magnetism in the Kondo lattice alloy CeCo1-xFexSi - Sereni, Julian Gustavo Renzo (2014)
Structural, magnetic, and thermal measurements performed on CeCo1-xFexSi alloys are reported. Three regions can be recognized: (i) Co rich (x <= 0.20) with a decreasing long-range antiferromagnetic order which vanishes at finite temperatures, (ii) an intermediate region (0.20 < x <= 0.30) showing a broad magnetic anomaly (C-A) in specific heat, and (iii) the nonmagnetic region progressively changing from a non-Fermi-liquid-type behavior towards a Fermi-liquid one as Fe concentration increases. The C-A anomaly emerges as an incipient contribution above T-N already at x = 0.10, which indicates that this contribution is related to short-range correlations likely of quasi-two-dimensional type. Both T-N transition and C-A anomaly are practically unaffected by an applied magnetic field up to B approximate to 10 T.